Monolithically integrated tri-axis shock accelerometers with MHz-level high resonant-frequency. (5th June 2017) - Zou, Hongshuo; Wang, Jiachou; Chen, Fang; Bao, Haifei; Jiao, Ding; Zhang, Kun; Song, Zhaohui; Li, Xinxin
Abstract: This paper reports a novel monolithically integrated tri-axis high-shock accelerometer with high resonant-frequency for the detection of a broad frequency-band shock signal. For the first time, a resonant-frequency as high as about 1.4 MHz is designed for all the x -, y - and z -axis accelerometers of the integrated tri-axis sensor. In order to achieve a wide frequency-band detection performance, all the three sensing structures are designed into an axially compressed/stretched tiny-beam sensing scheme, where the p + -doped tiny-beams are connected into a Wheatstone bridge for piezoresistive output. By using ordinary (1 1 1) silicon wafer (i.e. non-SOI wafer), a single-wafer based fabrication technique is developed to monolithically integrate the three sensing structures for the tri-axis sensor. Testing results under high-shock acceleration show that each of the integrated three-axis accelerometers exhibit about 1.4 MHz resonant-frequency and 0.2–0.4 µ V/V/g sensitivity. The achieved high frequencies for all the three sensing units make the tri-axis sensor promising in high fidelity 3D high-shock detection applications.